Plastid tubules in higher plants: an analysis of form and function - Waters, Mark T. (2004)
Besides photosynthesis, plastids are responsible for starch storage, fatty acid biosynthesis and nitrate metabolism. Our understanding of plastids can be improved with observation by microscopy, but this has been hampered by the invisibility of many plastid types. By targeting green fluorescent protein (GFP) to the plastid in transgenic plants, the visualisation of plastids has become routinely possible. Using GFP, motile, tubular protrusions can be observed to emanate from the plastid envelope into the surrounding cytoplasm. These structures, called stromules, vary considerably in frequency and length between different plastid types, but their function is poorly understood.